AFFRICATES, NASAL-OBSTRUENT SEQUENCES AND PHRASAL ACCENT IN TAJIO - Luh Anik Mayani (Linguistik Indonesia, 2016)
Among twenty consonants found in Tajio, /tʃ/ and /dʒ/ need a further observation because in Tomini-Tolitoli languages they have been analyzed differently by different researchers. The differences pertain both to the place and manner of articulation. Aspects of Tajio phonology discussed here are nasal-obstruent sequences as well as phrasal accent. Initial nasal-obstruent sequences contradict the sonority sequencing generalization (SSG). The sequence of nasal+obstruent can be interpreted in two ways: as a prenasalized consonant or as a consonant cluster. Tajio does not have lexical (word) stress; rather, it has a phrasal accent. Without lexical stress, the presence of the pitch accent depends on the location of the syllable within the intonational phrase.